Nitro-fatty acids: electrophilic signaling molecules in plant physiology - Di Fino, Luciano Martin (2021)
Main conclusion: Nitro fatty acids (NO2-FA)have relevant physiological roles as signaling molecules in biotic and abiotic stress, growth, and development, but the mechanism of action remains controversial. The two main mechanisms involving nitric oxide release and thiol modification are discussed. Abstract: Fatty acids (FAs) are major components of membranes and contribute to cellular energetic demands. Besides, FAs are precursors of signaling molecules, including oxylipins and other oxidized fatty acids derived from the activity of lipoxygenases. In addition, non-canonical modified fatty acids, such as nitro-fatty acids (NO2-FAs), are formed in animals and plants. The synthesis NO2-FAs involves a nitration reaction between unsaturated fatty acids and reactive nitrogen species (RNS). This review will focus on recent findings showing that, in plants, NO2-FAs such as nitro-linolenic acid (NO2-Ln) and nitro-oleic acid (NO2-OA) have relevant physiological roles as signaling molecules in biotic and abiotic stress, growth, and development. Moreover, since there is controversy on mechanisms of action of NO2-FAs as signaling molecules, we will provide evidence showing why this aspect needs further evaluation.